Discrimination and other barriers to accessing health care: perspectives of patients with mild and moderate intellectual disability and their carers. - Afia Ali; Katrina Scior; Victoria Ratti; Andre Strydom; Michael King; Angela Hassiotis (PLoS ONE)
Background People with intellectual disability have a higher prevalence of physical health problems but often experience disparities in accessing health care. In England, a number of legislative changes, policies and recommendations have been introduced to improve health care access for this population. The aim of this qualitative study was to examine the extent to which patients with intellectual disability and their carers experience discrimination or other barriers in accessing health services, and whether health care experiences have improved over the last decade years. Method and main findings Twenty nine participants (14 patient and carer dyads, and one carer) took part in semi-structured interviews. The interviews were audio-taped and transcribed and analysed using thematic analysis. Eight themes were identified. Half the participants thought that the patient had been treated unfairly or had been discriminated against by health services. There were accounts of negative staff attitudes and behaviour, and failure of services to make reasonable adjustments. Other barriers included problems with communication, and accessing services because of lack of knowledge of local services and service eligibility issues; lack of support and involvement of carers; and language problems in participants from minority ethnic groups. Most participants were able to report at least one example of good practice in health care provision. Suggestions for improving services are presented. Conclusion Despite some improvements to services as a result of health policies and recommendations, more progress is required to ensure that health services make reasonable adjustments to reduce both direct and indirect discrimination of people with intellectual disability.